(untitled) (Global Journal of Human-Social Science, 2021)
This article will deal with the problem of identity based on Nietzschean philosophy. We will try to approach how the theme is within a historicist approach, in parallel, describing how Nietzsche positions himself in relation to the problem in question. We will approach how Nietzsche values the body as a criterion for an individual identity distinct from a collective identity in which consciousness presents itself as a psychosocial criterion in order to typify human life. Likewise, we will emphasize the theme with its definition of free spirit described in Human too human, which, according to our understanding, best corresponds to the definition of the subject’s authenticity in the face of the cultural impositions of tradition.